Predictors of mortality in necrotizing fasciitis - Mahendra Kumar; Mohan Lal (Formosan Journal of Surgery, 2021)
Background: Necrotizing fasciitis (NF) is a rapidly progressing life threatening necrosis of the fascia and subcutaneous tissue. This study was done to assess the clinical presentation, laboratory investigations, microbiological characteristics, and major predictors of mortality associated with NF. Material and Methods: A prospective study was conducted from March 2013 to February 2014. NF patients were categorized into two groups based on their in hospital outcome. Demographic data, clinical features, comorbidities, site of infection with microbiology and laboratory results, and surgical intervention for patients were compared and analyzed. SPSS 26.0 statistics software was used for statistical analysis. Results: The mean age was 48.6 ± 16.78 years. Fever (P = 0.0177), tachycardia (P = 0.0155), and septic shock (P = 0.0046) were significantly high in nonsurvivors. Diabetes was the most common comorbidity. Renal impairment (P = 0.0229) was significantly high in the nonsurvivor group. The most common site was lower limb/thigh NF. Abdomen/groin NF (P = 0.0158) was significantly high in nonsurvivors. Nonsurvivors had significantly low hemoglobin (P = 0.0027) and serum sodium (P = 0.0023) and had significantly high leukocyte count (P = 0.00001), serum creatinine (P = 0.0000), serum glucose (P = 0.00003), and LRINEC score (P = 0.00002). Polybacterial infections (P = 0.021) were significantly high in nonsurvivors. The frequency of debridement more than 2 (P = 0.0469) and debridement within 24 h of admission (0.0013) were significantly high in survivors. Hospital stay (P = 0.0272) was significantly high in nonsurvivors. Multivariate logistic regression analysis did not show any independent factors associated with mortality Conclusion: Identification of predictors of mortality can improve the management and outcome of NF.